Increased Thermal Challenges Differentially Modulate Neural Plasticity and Stress Responses in Post-Smolt Atlantic Salmon (Salmo salar) - Tang, P. A.; Gharbi, N.; Nilsen, T. O.; Gorissen, M.; Stefansson, S. O.; Ebbesson, L. O. E. (Frontiers in Marine Science, 2022)
The successful transfer of farmed post-smolt Atlantic salmon (Salmo salar) depends on proper stress responses and cognitive functions during the early seawater (SW) phase. However, with increasing summer oceanic temperatures, these processes may become a challenge, implicating allostasis and welfare. Therefore, we examined the effect of post-smolt transfer from 10°C SW to elevated temperatures (13°C, 16°C, and 18°C) on plasma cortisol and telencephalic genes modulating cognition (neurod, bdnf, pcna, and c-fos) and stress-axis regulation (crf, crfbp, mr, gr1, gr2, and hsd11b2). Fish were sampled at i) 1 day following transfer, ii) 45 days of acclimation, and iii) 45 days and 1 h after an acute challenge test (ACT) using confinement stress. Fish transferred to 13°C retained stress responses, elevating levels of cortisol, crf, mr, gr2, c-fos, and bdnf and maintaining levels of neurod and pcna. Contrastingly, although cortisol increased at 16°C, telencephalic genes reverted to an inhibition of stress responses, increasing crfbp and gr1 complemented with dampened bdnf, neurod, and c-fos responses. However, transferring post-smolts to 18°C showed the most adverse effects, having absent stress responses (cortisol and c-fos), elevated crfbp, and a suppression of hsd11b2 and neurod. The hsd11b2 downregulation implies low cortisol inhibition in line with absent modulations in corticosteroid receptors and stress responses. These results suggest that the transfer to 16°C and 18°C inhibits the normal reactive response of post-smolts. Following acclimation (45 days), cortisol levels were basal for all groups; however, post-smolts at 16°C and 18°C maintained a telencephalic inhibition of key regulatory genes (crf, mr, gr2, and hsd11b2), alongside a lower mr/gr1 ratio, an indicator of chronic allostatic load. Moreover, neural plasticity (neurod and pcna) was suppressed at 16°C and 18°C, suggesting impacts of elevated allostatic loads with potentially inferior cognitive capacities. Despite maintaining similar plasma cortisol responses to ACTs, post-smolts at 16°C and 18°C elevated neural activation (c-fos) to stress, implying greater challenges, with the 18°C group also elevating the level of bdnf. In summary, the telencephalon shows that post-smolts transferred to 16°C and 18°C continue to struggle with the thermal allostatic loads even after acclimation, which is not revealed by plasma cortisol levels, grounding the importance of telencephalic measures in identifying environmental thresholds and hidden challenges.